Perencanaan Pembangkit Listrik Tenaga Surya (PLTS) On-Grid Dengan Sistem DC Coupling Berkapasitas 17 kWP Pada Gedung - Slamet Hani; Gatot Santoso; Subandi; Nur Arifin (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2020)
Solar energy which is abundant in the territory of Indonesia has not been utilized optimally, while the demand for electricity which is increasing day by day means that electricity from PLN does not allow to meet the demand throughout Indonesia. If the community takes part in protecting this earth by trying to produce their own electricity with the PLTS (Solar Power Plant) system, both On-Grid and OffGrid systems, so that it can reduce the negative impact of thermal power plants commonly used today in various side of lifePLTS planning and simulation were carried out using the PvSyst 6.8.4 software then analyzed and the results were in the form of a structured report, with certain formulations according to the required parameters starting from the estimated power requirements. The validity of the data in an act of research or inspection obtains the accuracy and validation of the data with the preliminary pre-design data, in this case the residential building blueprint in the accuracy of the installation of the number of photovoltaics onthe roof of the building. The results showed that PLTS has a system performance of 75.4% which can meet 42.16% of the total electricity demand that is estimated to be served by PLTS or in other words it meets 34.01% of the total electricity needs of the Graha Cendekia Yogyakarta building.